Psychological foundations of military motivation in the context of historical transformations - OSYODLO, Vasyl (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The issue of a soldier's combat motivation is crucial for military psychology and the historical understanding of human behavior in war. It depends on internal and external factors that shape moral choices, resilience, and cooperation in combat situations. The contemporary hybrid war in Ukraine emphasizes the importance of motivation for a soldier's psychological endurance.Methods. The study uses the following theoretical methods: content analysis of historical and current texts on military motivation; comparative-historical analysis of motivational changes over different periods; qualitative analysis with grounded theory (open and axial coding); and quantitative analysis through Likert-scale surveys.Results. It has been found that by the early 21st century, large interstate wars – along with their ideologies, patriotism, and jus in bello – were considered obsolete, supplanted by hybrid conflicts. However, the ongoing Russian-Ukrainian war has shown that large-scale wars are still relevant. The question of a soldier's motivation, which has evolved from honor and glory in ancient times, through medieval religious duty, to ideology and cohesion in the 20th century, is once again at the forefront. Recent research emphasizes factors such as identity, the value of service, and psychological preparedness. A retrospective analysis provides a deeper understanding of why individuals go to war and how morale can be maintained amid new hybrid threats.Conclusions. A retrospective analysis of soldier motivation across different eras reveals a transformation in the meaning of participation in war – ranging from ancient valor, medieval religious duty, and modern discipline to a multifactorial, conscious motivation in the 21st century. In the current Ukrainian context, there is a rise in internal motivation based on personal responsibility, moral choice, and national identity; an increased role for combat cohesion and psychological support; and an understanding of service as part of a broader civilizational choice. All these factors make the motivation of Ukrainian soldiers not just an adaptive response but a driving force in the ongoing struggle for freedom, dignity, and a place in the European world.
Keywords: soldier motivation; historical periods; internal motivation; national identity; combat cohesion; psychological support; civilizational choice; Ukrainian context; freedom; dignity